Effect of elevated temperature on indentation response of glass/epoxy laminates hybridised with milled fibres. (6th January 2023) - Saravanakumar, K.; Kumar, C. Suresh; Arumugam, V.
This work investigates the effect of elevated temperature on quasi-static indentation response of glass/epoxy laminates. The glass/epoxy laminates with cross-ply [0/90]3S configuration were fabricated by hand lay-up technique and subjected to quasi-static indentation test at elevated temperature of 60°C and 90°C. Furthermore, the glass/epoxy laminates were hybridised with milled glass fibres to enhance the indentation resistance. The contact stiffness, peak load, and permanent dent induced during indentation were evaluated and correlated with unmodified glass/epoxy laminates. Furthermore, the residual load resistance was assessed by conducting three point bending test. Results show that the rise in elevated temperature drastically decreased the peak force, and contact stiffness by an average of 50% and 70%, respectively. Whereas at 30°C, the glass/epoxy laminates modified with milled fibres show greater potential in peak load and contact stiffness by an average of 40% and 50%. Filler debonding/pullout toughening mechanisms attributes to the improvement in peak force, and contact stiffness. It was also found that as the permanent dent grows larger, the residual load bearing capability decreases.